Electrolytes for electrochemical energy storage. (3rd January 2017) - Xia, Lan; Yu, Linpo; Hu, Di; Chen, George Z.
Abstract : Innovative salt solutions and liquid salts can advance batteries, supercapacitors, and supercapatteries for stationary, transport, seasonal and regional energy storage. Abstract : An electrolyte is a key component of electrochemical energy storage (EES) devices and its properties greatly affect the energy capacity, rate performance, cyclability and safety of all EES devices. This article offers a critical review of the recent progress and challenges in electrolyte research and development, particularly for supercapacitors and supercapatteries, rechargeable batteries (such as lithium-ion and sodium-ion batteries), and redox flow batteries (including fuel cells in a broad sense). The review will focus on liquid electrolytes, including aqueous and organic electrolytes, ionic liquids and molten salts. The influence of electrolyte properties on the performances of different EES devices is discussed in detail.